Paediatric MOG antibody–associated ADEM with complex movement disorder: A case report. (January 2019) - Sa, Mario; Thornton, Rachel; Chong, WK Kling; Kaliakatsos, Marios; Hacohen, Yael
Myelin oligodendrocyte glycoprotein antibodies (MOG-Abs) are a well-recognized cause of acquired demyelinating syndromes in both adult and children. Despite basal ganglia involvement on imaging, movement disorder is not a cardinal feature. We describe a 2-year-9-month-old girl who presented with severe encephalopathy with aphasia, seizures and a complex movement disorder with dystonic posturing and tonic eye deviation. Neuroimaging revealed subtle asymmetrical predominantly white matter signal changes. MOG-Abs were positive in the serum. Other known pathogenic autoantibodies including N-methyl-D-aspartate receptor antibodies (NMDAR-Abs) were negative. The patient made a complete recovery following 2-week corticosteroid treatment. This case highlights the need for MOG-Ab testing in children with suspected autoimmune encephalopathies.